FA-LAR: an efficient flow aware based load adaptive routing scheme for optical communication networks - Madhu Mohan Swaminathan, S; K. Sakthivel, N; Subasree, S (International Journal of Engineering and Technology, 2018)
Routing Protocols have been proposed to enable the network to identify and suggest various routes to number of demanded flows. In the Flow-Aware Network Models, the routes are identified and selected with the help of Flow Tables or Flow Identifiers that proposed by Flow Aggregation Mechanism. That is, users can define a Flow Aggregation Model to suggest routes depend on their defined-demanded flows and this model effectively handles many flows, which helps core routers to profit aggregate routing. This is an efficient and effective approach to identify a best route to achieve required performance. It is noted from the literature survey that the Flow-Aware Multi-Topology Adaptive Routing (FAMTAR) was proposed for achieving higher Network performance through multipath solutions. This FAMTAR Model was implemented and studied thoroughly. From the experimental results, it was noticed that this model unable to i. detect and manage bulk flow, ii. Control Traffic Loss and iii. Maintain Deviation of Links Load against Traffic Load. To address the above mentioned issues, this research work is proposed an efficient Flow-Aware based Load Adaptive Routing (FA-LAR). This model is developed and implemented in ns3 and the simulation results are analysed carefully. From the experimental results, it is noticed that the prosed Model, FA-LAR is performing well as compared with the existing FAMTAR in terms of Queueing Delay, Throughput, Power Consumption (Energy Dissipation), and Load Deviation. It is also noticed that the proposed model unable to achieve higher Throughput for Low Load.Â Â